The effect of renin–angiotensin system blockade on renal protection in chronic kidney disease patients with hyperkalemia. (December 2014) - Lee, Ju-Hyun; Kwon, Young Eun; Park, Jung Tak; Lee, Mi Jung; Oh, Hyung Jung; Han, Seung Hyeok; Kang, Shin-Wook; Choi, Kyu Hun; Yoo, Tae-Hyun
Hypothesis: The aim of this study was to determine the effects of renin–angiotensin system (RAS) blockade maintenance on renal protection in chronic kidney disease (CKD) patients with hyperkalemia occurring during treatment with RAS blockade. Materials and methods: CKD III or IV patients, who were prescribed with RAS blockers and also had hyperkalemia, were included. The study population was divided into two groups based on maintenance or withdrawal of RAS blocker. Renal outcomes (doubling of creatinine or end-stage renal disease) and incidence of hyperkalemia were compared between the two groups. Results: Out of 258 subjects who developed hyperkalemia during treatment with RAS blockers, 150 (58.1%) patients continued on RAS blockades, while RAS blockades were discontinued for more than 3 months in the remaining 108 patients. Renal event-free survival was significantly higher in the maintenance group compared with the withdrawal group. Cox proportional hazard ratio for renal outcomes was 1.35 (95% CI: 1.08–1.92, p =0.04) in the withdrawal group compared with the maintenance group. However, the incidence of hyperkalemia and hyperkalemia-related hospitalization or mortality did not differ between the two groups. Conclusions: This study demonstrated that the maintenance of RAS blockade is beneficial for the preservation of renal function and relatively tolerable in patients with CKD and hyperkalemia occurring during treatment with RAS blockade.